2021
DOI: 10.1111/jfd.13536
|View full text |Cite
|
Sign up to set email alerts
|

Virus infections of the European Eel in North Rhine Westphalian rivers

Abstract: The panmictic population of the European eel Anguilla anguilla is declining dramatically throughout its distribution range since the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These duplication events, genetic raw materials were provided to facilitate new adaptations to the changing environment 65 . The duplicated gene functions of eels are immune-related to respond against different pathogens, which has been linked to the major factor contributing to the decline of eel populations 4,19,53 . Presumably, physiological fitness for adaptation might have been weakened by changes in the ecological environment, causing these evolutionary novelties 5 .…”
Section: Discussionmentioning
confidence: 99%
“…These duplication events, genetic raw materials were provided to facilitate new adaptations to the changing environment 65 . The duplicated gene functions of eels are immune-related to respond against different pathogens, which has been linked to the major factor contributing to the decline of eel populations 4,19,53 . Presumably, physiological fitness for adaptation might have been weakened by changes in the ecological environment, causing these evolutionary novelties 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Eel viruses have been detected in both wild and farmed eels (van Beurden et al, 2012;Danne et al, 2022;Haenen et al, 2010).…”
Section: Virusesmentioning
confidence: 99%
“…Eel viruses have been detected in both wild and farmed eels (van Beurden et al., 2012; Danne et al., 2022; Haenen et al., 2010). Viruses are particularly problematic because of their ability to remain dormant, to spread through seemingly healthy populations and become virulent under certain conditions (Haenen et al., 2009).…”
Section: Eel Pathogens Damages and Symptomsmentioning
confidence: 99%
“…Primers and probes sequences are listed in Table 2. The target for detection of EPV-1 is a fragment of the 2C gene, primers were described recently (Danne et al, 2021). EPV-1 probe was deduced from the published EPV-1 sequence NC_022332.1 (Fichtner et al, 2013).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…In 2013 a study demonstrated the infection of a diseased yellow eel with a novel picornavirus (EPV-1) in Lake Constance (Fichtner et al, 2013). Currently, EPV-1 was isolated from elvers and yellow eels caught in the Rhine system in Germany (Danne et al, 2021). Knowledge about some virus infections of eels is still at the beginning and to date, some findings of eel viruses come from other eel species.…”
mentioning
confidence: 99%